Seasonal phytoplankton dynamics in extreme southern South America (Beagle Channel, Argentina) - Almandoz, Gaston Osvaldo (2011)
The phytoplankton biomass and composition dynamics in relation with environmental factors were explored during an annual cycle (July 2006–2007) for the first time in the Beagle Channel. Samples were examined by light and scanning electron microscopy and carbon biomass was estimated using measured cell biovolumes. The annual cycle was characterized by a sharp contrast between low density and biomass during the autumn–winter period and a significant increase during spring and summer. The maximum biomass peak was observed during early spring (141 μg C l− 1 and 8.7 μg Chl a l− 1) and was associated with a bloom of the diatom genus Chaetoceros. In spite of a strong nutrient depletion that lead to the subsequent bloom decline, a second peak of biomass was observed after 2 weeks, mainly represented by the diatoms T. mendiolana and T. anguste-lineata. Towards the end of spring and during summer diatom density decreased and assemblages were enriched by unidentified tiny phytoflagellates and dinoflagellates. A total of 138 taxa were identified during the study period. From these, 10 are known as potentially toxic species: Alexandrium catenella, A. ostenfeldii, A. tamarense, Dinophysis acuminata, D. rotundata, Prorocentrum cordatum, Pseudo-nitzschia australis, P. calliantha, P. fraudulenta and P. cf. seriata. Their presence is noteworthy since the area sustains a growing aquiculture production.